Reengineering Component-Based Software Systems with Archimetrix - von Detten, Markus; Platenius, Marie Christin; Becker, Steffen (Journal of Software and Systems Modeling)
Many software development, planning, or analysis tasks require an up-to-date software architecture documentation. However, this documentation is often outdated, unavailable, or at least not available as a formal model which analysis tools could use. Reverse engineering methods try to fill this gap. However, as they process the system’s source code, they are easily misled by design deficiencies (e.g., violations of component encapsulation) which leaked into the code during the system’s evolution. Despite the high impact of design deficiencies on the quality of the resulting software architecture models, none of the surveyed related works is able to cope with them during the reverse engineering process. Therefore, we have developed the Archimetrix approach which semi-automatically recovers the system’s concrete architecture in a formal model while simultaneously detecting and removing design deficiencies. We have validated Archi metrix on a case-study system and two implementation variants of the CoCoME benchmark system. Results show that the removal of relevant design deficiencies leads to an architecture model which more closely matches the system’s conceptual architecture.

Reducing Energy Consumption of Radio Access Networks - Herlich, Matthias
Radio access networks (RANs) have become one of the largest energy consumers of communication technology [LLH+13] and their energy consumption is predicted to increase [FFMB11]. To reduce the energy consumption of RANs different techniques have been proposed. One of the most promising techniques is the use of a low-power sleep mode. However, a sleep mode can also reduce the performance. In this dissertation, I quantify how much energy can be conserved with a sleep mode and which negative effects it has on the performance of RANs. Additionally, I analyze how a sleep mode can be enabled more often and how the performance can be kept high. First, I quantify the effect of power-cycle durations on energy consumption and latency in an abstract queuing system. This results in a trade-off between energy consumption and latency for a single base station (BS). Second, I show that considering a network as a whole (instead of each BS individually) allows the energy consumption to be reduced even further. After these analyses, which are not specific for RANs, I study RANs for the rest of the dissertation. RANs need to both detect and execute the requests of users. Because detection and execution of requests have different requirements, I analyze them independently. I quantify how the number of active BSs can be reduced if the detection ranges of BSs are increased by cooperative transmissions. Next, I analyze how more BSs can be deactivated if the remaining active BSs cooperate to transmit data to the users. However, in addition to increasing the range, cooperative transmissions also radiate more power. This results in higher interference for other users which slows their transmissions down and, thus, increases energy consumption. Therefore, I describe how the radiated power of cooperative transmissions can be reduced if instantaneous channel knowledge is available. Because the implementation in real hardware is impractical for demonstration purposes, I show the results of a simulation that incorporates all effects I studied analytically earlier. In conclusion, I show that a sleep mode can reduce the energy consumption of RANs if applied correctly. To apply a sleep mode correctly, it is necessary to consider power-cycle durations, power profiles, and the interaction of BSs. When this knowledge is combined the energy consumption of RANs can be reduced with only a slight loss of performance. Because this results in a trade-off between energy consumption and performance, each RAN operator has to decide which trade-off is preferred.

Re-Chord: A Self-stabilizing Chord Overlay Network - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Theory of Computing Systems)
The Chord peer-to-peer system is considered, together with CAN, Tapestry and Pastry, as one of the pioneering works on peer-to-peer distributed hash tables (DHT) that inspired a large volume of papers and projects on DHTs as well as peer-to-peer systems in general. Chord, in particular, has been studied thoroughly, and many variants of Chord have been presented that optimize various criteria. Also, several implementations of Chord are available on various platforms. Though Chord is known to be very efficient and scalable and it can handle churn quite well, no protocol is known yet that guarantees that Chord is self-stabilizing, i.e., the Chord network can be recovered from any initial state in which the network is still weakly connected. This is not too surprising since it is known that the Chord network is not locally checkable for its current topology. We present a slight extension of the Chord network, called Re-Chord (reactive Chord), that turns out to be locally checkable, and we present a self-stabilizing distributed protocol for it that can recover the Re-Chord network from any initial state, in which the n peers are weakly connected, in O(nlogn) communication rounds. We also show that our protocol allows a new peer to join or an old peer to leave an already stable Re-Chord network so that within O(logn)^2) communication rounds the Re-Chord network is stable again.

Randomized Online Algorithms for Set Cover Leasing Problems - Abshoff, Sebastian; Markarian, Christine; Meyer auf der Heide, Friedhelm (Proceedings of the 8th Annual International Conference on Combinatorial Optimization and Applications (COCOA))
In the leasing variant of Set Cover presented by Anthony et al.[1], elements U arrive over time and must be covered by sets from a familyF of subsets of U. Each set can be leased for K different periods of time.Let |U| = n and |F| = m. Leasing a set S for a period k incurs a cost ckS and allows S to cover its elements for the next lk time steps. The objectiveis to minimize the total cost of the sets leased, such that elements arrivingat any time t are covered by sets which contain them and are leased duringtime t. Anthony et al. [1] gave an optimal O(log n)-approximation forthe problem in the offline setting, unless P = NP [22]. In this paper, wegive randomized algorithms for variants of Set Cover Leasing in the onlinesetting, including a generalization of Online Set Cover with Repetitionspresented by Alon et al. [2], where elements appear multiple times andmust be covered by a different set at each arrival. Our results improve theO(log2(mn)) competitive factor of Online Set Cover with Repetitions [2]to O(log d log(dn)) = O(logmlog(mn)), where d is the maximum numberof sets an element belongs to.

Quality of Service in Network Creation Games - Cord-Landwehr, Andreas; Mäcker, Alexander; Meyer auf der Heide, Friedhelm (Proceedings of the 10th International Conference on Web and Internet Economics (WINE))
Network creation games model the creation and usage costs of networks formed by n selfish nodes. Each node v can buy a set of edges, each for a fixed price α > 0. Its goal is to minimize its private costs, i.e., the sum (SUM-game, Fabrikant et al., PODC 2003) or maximum (MAX-game, Demaine et al., PODC 2007) of distances from v to all other nodes plus the prices of the bought edges. The above papers show the existence of Nash equilibria as well as upper and lower bounds for the prices of anarchy and stability. In several subsequent papers, these bounds were improved for a wide range of prices α. In this paper, we extend these models by incorporating quality-of-service aspects: Each edge cannot only be bought at a fixed quality (edge length one) for a fixed price α. Instead, we assume that quality levels (i.e., edge lengths) are varying in a fixed interval [βˇ,β^] , 0 series = LNCS

PBlaman: performance blame analysis based on Palladio contracts - Brüseke, Frank; Wachsmuth, Henning; Engels, Gregor; Becker, Steffen (Proceedings of the 4th International Symposium on Autonomous Minirobots for Research and Edutainment)

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Programs from Proofs -- Approach and Applications - Wonisch, Daniel; Schremmer, Alexander; Wehrheim, Heike (Proceedings of the Software Engineering Conference (SE))
Proof-carrying code approaches aim at safe execution of untrusted code by having the code producer attach a safety proof to the code which the code consumer only has to validate. Depending on the type of safety property, proofs can however become quite large and their validation - though faster than their construction - still time consuming. In this paper we introduce a new concept for safe execution of untrusted code. It keeps the idea of putting the time consuming part of proving on the side of the code producer, however, attaches no proofs to code anymore but instead uses the proof to transform the program into an equivalent but more eﬃciently veriﬁable program. Code consumers thus still do proving themselves, however, on a computationally inexpensive level only. Experimental results show that the proof eﬀort can be reduced by several orders of magnitude, both with respect to time and space.

Privacy-Preserving Reputation Management - Petrlic, Ronald; Lutters, Sascha; Sorge, Christoph (Proceedings of the 29th Symposium On Applied Computing (SAC))
Reputation systems provide reputation values of rated parties to users. These reputation values, typically aggregations of individual user ratings, shall be reliable, i.e. should enable a realistic assessment of the probability that the rated party behaves as expected in a transaction. In order for the reputation values to stay reliable and, thus, for the reputation system to provide a beneﬁt, the system needs to be resistant against manipulations by users, the rated parties trying to improve their reputation values, and even against competitors trying to worsen a reputation value. At the same time, a reputation system shall provide privacy protection for users: rated parties shall not be able to learn who provided a certain rating. Otherwise users might not take part in the system as they fear bad feedback in revenge for bad ratings, or users do not want to be connected to certain transactions based on their provided ratings. In this paper we come up with a solution that provides both, reliability of reputation values on the one hand, and privacy protection for users on the other hand. In contrast to related work, our solution only makes use of a single reputation provider that needs to be trusted (to a certain extent) and does not require any bulletin boards to be present in the system. We make use of the Paillier cryptosystem to provide an aggregation of individual user ratings in a way that no party can learn which user provided a certain rating.

Privacy-Preserving Multiparty Digital Rights Management - Petrlic, Ronald